Do fluoroquinolones increase aortic aneurysm or dissection incidence and mortality? A systematic review and meta-analysis - Chen, Can; Patterson, Benjamin; Simpson, Ruan; Li, Yanli; Chen, Zhangzhang; Lv, Qianzhou; Guo, Daqiao; Li, Xiaoyu; Fu, Weiguo; Guo, Baolei (Frontiers in Cardiovascular Medicine, 2022)
Objective The aim of this study was to determine the association between fluoroquinolones (FQs) use, the risk of de novo aortic aneurysm or dissection (AAD), and the prognosis of patients with pre-existing AAD. Materials and methods We searched PubMed, EMBASE, CENTRAL, Scopus, and Web of Science on 31 March 2022. Observational studies that evaluated the association of FQs with AAD risk in the general population or FQs with the prognosis of patients with preexisting AAD and presented adjusted effect estimates were included. Two reviewers assessed study eligibility, extracted data, and assessed the risk of bias and certainty of evidence using GRADE. Results Of the 13 included studies, 11 focused on the association of FQs with de novo AAD incidence, and only one study investigated the association of FQs with the patient with AAD prognosis. FQ use was associated with an increased risk of de novo AAD within 30 days (RR: 1.42; 95% CI: 1.11–1.81; very low certainty) and 60 days (RR: 1.44; 95% CI: 1.26–1.64; low certainty). Specifically, the association was significant when compared with amoxicillin, azithromycin, doxycycline, or no antibiotic use. Furthermore, patients with preexisting AAD exposure to FQ had an increased risk of all-cause mortality (RR: 1.61; 95% CI: 1.50–1.73; moderate certainty) and aortic-specific mortality (RR: 1.80; 95% CI: 1.50–2.15; moderate certainty), compared to the non-exposed FQ group within a 60-day risk period. Conclusion FQs were associated with an increased incidence of AAD in the general population and a higher risk of adverse outcomes in patients with preexisting AAD. Nevertheless, the results may be affected by unmeasured confounding factors. This should be considered by physicians contemplating using FQs in patients with aortic dilation and those at high risk of AAD. Systematic Review Registration [https://www.crd.york.ac.uk/prospero/], identifier [CRD42021230171].